(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Investment attracts different types of investors for different reasons. There are two major types of investors in the capital market, the institutional investor and the retail investor. Institutional investors are businesses or organisations having staff members who make investments on behalf of others (typically, other companies and organizations). Retail investors, on the other hand, are those who make investments with their own money, usually for themselves. Over the past few years, it has been the boom time for retail participants in the capital markets trading, as a record number of new participants have been added to the NSE and BSE. The present study helps to find the growth of retail investors, and different factors affecting the growth of retail individual investors and to study the Incremental growth of the Demat account in past few years which reflect the interest of investors in the capital market.